English methods of birth control - Sanger, Margaret, 1879-1966
1915 1915 1910s 18 pages 17 near to the womb about ten minutes before connection, so that it is dissolved. On rising in the morning she syringes herself well out with water or one of the solutions before mentioned. 3. The Cotton-wool Plug.— This cheap and simple method is recommended by a high medical authority. Get from a chemist some cotton-wool (about 8 cents per ¼ lb. packet), ½ lb. of vaseline (about 25 cents a lb.), and ½ oz. of boric acid powder. Mix the powder and the vaseline very thoroughly together, or get the chemist to do so ; the mixture can be kept in a jam-pot. Make a cotton-wool ball about the size of an egg, and tie the end of a piece of twine or tape tightly round it. Before retiring dip the ball into the borated vaseline (or carbolated vaseline), so as to smear it all over, and then slip it into the passage as high up as it will go, leaving several inches of the twine or tape hanging out. The plug can be drawn out immediately after intercourse or next morning. (A woman who has borne many children may have her passage so enlarged as to need a larger plug than the above.) 4. The Mensinga or Check Pessary.— When properly used, this is one of the most satisfactory arrangements for a woman who has already had one or more children, but it requires a little more intelligent adjustment than the others ; and it is almost indispensable to have the advice of a doctor or trained nurse as to how to fit and introduce it (people should urge their doctors to give this advice). It consists of a little indiarubber cup or cap with a thick, springy rim, and costs about 60 cents. If a finger be carefully introduced into the wife's passage, there will be felt high up what seems to be a smooth ball with a little hole in it. This smooth ball is the bottom of the womb. The womb is really like a pear with the narrow end downward, except that there is a little hole where the stalk of the pear would be. In order to prevent conception it is necessary that the male fluid should not enter this hole into the womb ; so the little cap or Mensinga Pessary covers over the bottom of the womb and prevents the fluid entering. In choosing one of these pessaries care should be taken to get the largest size that can be worn with comfort. A woman who has had a number of children will generally need a larger one than a woman who has had only one or two. To introduce the pessary it should be wetted and slightly soaped, and the rim should then be clipped between the finger and thumb so as to make the cap a narrow oval, with the soft part downwards. It should then be slipped into the passage and carefully guided until it is felt to cover the whole of the bottom of the womb, and to be in such a position that the edge of the pessary fills the passage. This can be done by the wife herself in the day time, so there is no need for any further precaution at night. At any convenient time on the following morning the wife should syringe herself as mentioned above, then remove the pessary, and syringe again thoroughly. If these operations are carefully performed, the method is very reliable and convenient. It interferes less with normal 15X/2/566/51